Pathogenetic and diagnostic role of osteoprotegerin in the combined course of osteoarthritis and obesity - Litvynova, A.; Pasiieshvili, L. (Journal of Education, Health and Sport, 2022)
In recent years, it has been proven that the formation of OA can occur against the background of impaired bone metabolism. Bone remodeling is considered as a continuous complex process aimed at eliminating microdamages and updating the bone matrix. A key link in the regulation of this process is the system RANK / RANKL / OPG (osteoprotegerin), which provides a balance of activity of osteoblasts and osteoclasts. It blocks the interaction between RANK and RANKL by intercepting the RANKL ligand, which inhibits osteoclast development and reduces bone resorption. Thus, these properties of OPG can be considered as one of the pathogenetic factors in patients with dystrophic joint lesions. Objective: to investigate the content and role of osteoprotegerin in young patients with osteoarthritis, which occurs against the background of changes in body weight. Materials and methods. The study involved 75 young patients (mean age - 30.92 ± 0.546 years) with overweight or obesity, who in the previous stages of the study was diagnosed with osteoarthritis (main group). The comparison group was represented by 50 patients with osteoarthritis and normal body weight. The age of patients was 30.95 ± 0.545 years; as in the previous group, men predominated - 64% and 36% respectively. Benchmarks of osteoprotegerin were obtained in a study of 37 relatively healthy individuals of the same age and sex. The level of osteoprotegerin was determined by enzyme-linked immunosorbent assay using the FineTest EH0247 reagent kit, China. The outcomes were processed by the methods of variation statistics using the computer program STATISTICA.Results and discussion. When determining the content of OPG in the serum of patients of the main group was found to increase to 124.03 pg / ml, against control - 65.64 pg / ml. In the group of patients with isolated OA, this value was 92.29 pg / ml. Meaning that, in OA, running on the background of altered BMI, the content of OPG is likely to increase, both in relation to the norm and the results of the comparison group (p <0,001). The formation and course of osteoarthritis is accompanied by an increase in osteoprotegerin, the content of which depends on the degree of obesity and the radiological stage of the process. Conclusions: The course of osteoarthritis is accompanied by an increase in osteoprotegerin, which is considered a negative regulator of bone resorption. In osteoarthritis, which occurs against the background of changes in body mass index, a direct correlation with the degree of obesity. Changes in osteoprotegerin in patients with osteoarthritis depend on the radiological stage of joint damage and are most pronounced in individuals with stage 2 obesity and stage 2 radiological changes